A Randomized, Double-Blind, Placebo-Controlled, Crossover Clinical Trial of Partially Hydrolyzed Guar Gum Dietary Fiber for the Improved Gut Microbiome in Healthy Athletes - Kapoor, Mahendra (Curr Dev Nutr, 2020)
OBJECTIVES: The widespread impact of the gut microbiota in human health has emerged in recent years. Changes in diet and exercise can alter the gut microbiomes of active athletes. We performed a randomized, controlled study to evaluate the relationship between the partially hydrolyzed guar gum (PHGG) prebiotic dietary fiber and the relative abundance of the gut microbiomes in the context of changes in lifestyle-related factors, and their significant correlation with fecal defecation characteristics in healthy athletes. METHODS: Subjects followed a daily 6 grams dietary intake of either PHGG or placebo for four weeks, following a three weeks washout period, subjects followed another four weeks of crossover alternative administration. Fecal defecation characteristics were assessed using a questionnaire along with the quality of life (QOL) questions and gut microbiome abundance was determined by 16S rRNA gene sequencing and real-time PCR analysis. RESULTS: The alteration in gastrointestinal microbiomes relative abundance was correlated to representative changes in fecal defecation characteristics, especially in ameliorating diarrhea (P = 0.035) and fecal excretory feeling (P = 0.038). The PHGG intake led to a significant increase in phylum Actinobacterium (P = 0.04), along with a significant decrease in Bacteroidetes (P = 0.036). A trending decrease in Firmicutes (P = 0.09) Awas noticed. Also, a significant alteration in the relative abundance of Bifidobacterium (P = 0.047) and Clostridium subcluster XI (P = 0.044) were observed with PHGG intake compared with placebo. Principal component analysis and hierarchical clustering analysis represented a clear overview of the distribution of quality of life covariates evaluated in the study. CONCLUSIONS: Improved diarrhea was associated with the relative abundance of phylum Firmicutes/Bacteroidetes ratio and genera Bacteroides/Prevotella ratio for the PHGG intervention compared to placebo. The finding reveals that even at relatively low dosage, intake of prebiotic PHGG fiber modulates gut microbiomes, and thus improves gastrointestinal health. Overall, the quality of lifestyle factors was significantly improved with PHGG consumption. FUNDING SOURCES: Taiyo Kagaku, University of Tsukuba, and Otsuma Women's University equally contributed to the study.